Not Just Objects: Alaska Native Material Culture at the McClung Museum of Natural History and Culture - Christine Johnson (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
As a curatorial intern at the McClung Museum at the University of Tennessee, I have come into contact with a collection of over one hundred pieces of material culture that originate from Native communities in what is now the state of Alaska. As a former resident of the state, I understand the diversity of the region’s Indigenous population, and am concerned with the common curatorial practice of lumping all Native Alaskan cultures into one monolithic group (i.e. “Eskimos). In museums, the usage of outdated and inaccurate terminology in identifying the material culture of these communities is a remnant of colonialism and is especially troublesome in a university setting . Through my work at the McClung Museum, I conclude that one of the first steps to eradicate this practice is to engage in community collaboration with members of source communities, especially artists and elders. This paper explores the origins of the misrepresentation of Indigenous people in American museums, the current situation as it pertains to Native Alaskan material culture, examples of successful community collaboration, and my research and collaboration processes with the McClung Museum’s Native Alaskan holdings.